Designing an intellectual property management information system for the University of the Philippines Manila Technology Transfer and Business Development Office - Llamzon, Roxanne B.; Talisayon, Serafin D. (Quezon City University of the Philippines Diliman, 2017)
It is imperative for the University of the Philippines (UP) to facilitate the dissemination of research outputs and innovations generated by its faculty and students. Technology transfer is the primary mechanism to fulfill UP's mandate to be both a research-intensive and public service-oriented national university. The audit and protection of intellectual property assets are the first steps to not only successful technology transfer, but also to building an innovation ecosystem in the university.
Information technology plays a key role in the efficient and effective execution of complex, multi-stakeholder processes, such as intellectual property management in UP Manila. To introduce improvements to the system, a preliminary investigation was conducted, leading to the determination of functional requirements, which were used as inputs to the definition of the overarching conceptual framework and design of the proposed solution - an intellectual property management information system.
In the proposed system, the intellectual property management information system simplifies the process by automatically performing 39% of tasks. With this design, it will be possible to have a single, electronic system to eliminate confusing processes and duplication of work; generate reports in an instant, on demand; increase transparency- because the information will be publicly available on the web; and potentially create a conducive channel for collaboration between the university and external partners.
The final output, which is expected by March 2018, is the working prototype of the intellectual property management information system.
In partial fulfillment of the requirements of TM 299
Thesis
Keywords: Information storage and retrieval systems -- Intellectual property -- Philippines; Technology transfer; Business development companies